Características da carcaça e da carne de novilhos suplementados sob pastejo de sorgo forrageiro, abatidos aos 18 meses de idade - Colvero, Perla Cordeiro de Paula (2016)
The objective of the present study was to evaluate the carcass and meat characteristics of beef cattle, kept in sorghum forage pasture (Sorghum bicolor (L) Moench) supplemented with different concentrate levels, .8%, 1.0% and 1.2% of live weight (LW), slaughtered with 18 months old. Samples of the meat of 24 beef steers, from Nelore and Charolais crossbreeding, with initial average age of 16 months and initial average weight of 334.58 ± 5.23 kg, were used. The completely randomized experimental design was used, with three treatments and eight repetitions, totalizing 24 experimental units. The levels of supplementation evaluated on this study for steers finished on sorghum pasture did not changed (P>.05) characteristics of the carcass, being observed an average slaughter weight of 414.90 kg. Among the characteristics that express carcass muscularity there are the conformation, cushion thickness, Longissimus dorsi area and arm perimeter, however, at the present study any of these variables suffered influence of the levels of supplementation (P>0.05). The variables related to meat characteristics were not influenced by the supplementary levels (P>0.05), being observed an average of 4.10 points for meat color, characterized as typical red. No differences were verified (P>0.05) for saturated fatty acid content on the meat of bovines finished with different levels of supplementation. There was a significant effect (P=.0203) of the levels of supplementation in sorghum pasture on the concentration of myristoleic acid (C14:1 n-5), being observed a decrease on its value with the increase of the level of supplementation, that may be associated to the myristoylated content on the meat. The content of the 10-heptadecenoic (C17:1 n-7 cis) and elaidic (C18:1 n-9 trans) acid on the meat of the animals kept in sorghum pasture was influenced (P<.05) by the levels of supplementation, being that the animals that received .8% LW were higher to the animals that received 1.0%, and the similarity was also observed in the animals that received 1.0% and 1.2% LW. The conjugated linoleic acid - CLA (C18:2 cis-9 trans-11) present at the meat of the steers was influenced by the supplementary levels, with values of .57%; .43% and .40% for the animals that received .8%; 1.0% and 1.2% of LW, respectively, benefiting the quality of the meat of the bovines finished in sorghum pasture receiving .8% LW. Regarding the omega-6 and omega-3 contents and the relationship between them, important variables to evaluate the lipid quality of the meat, were not influenced by the diet (P>.05).